Human olfactory stem cells for injured facial nerve reconstruction in a rat model. (1st February 2016) - Batioglu–Karaaltin, Aysegul; Karaaltin, Mehmet Veli; Oztel, Olga Nehir; Ovali, Ercument; Sener, Belit Merve; Adatepe, Turgut; Yigit, Ozgur; Bozkurt, Erol; Baydar, Serap Yesilkir; Bagirova, Melahat; Uzun, Nurten; Allahverdiyev, Adil
Abstract: Background: The purpose of this study was to show the efficacy of olfactory stem cells for injured facial nerve reconstruction in a rat model. Methods: Olfactory stem cells were isolated from the olfactory mucosa of human participants. A 2‐mm excision was performed on the right facial nerve of all rats. Reconstruction was performed with a conduit in group 1 ( n = 9); a conduit and phosphate‐buffered saline in group 2 ( n = 9); and a conduit and labeled olfactory stem cell in group 3 ( n = 9). Rats were followed for whisker movements and electroneuronography (ENoG) analyses. Results: The whisker‐movement scores for group 3 were significantly different from other groups ( p < .001). ENoG showed that the amplitude values for group 3 were significantly different from group 1 and group 2 ( p = .030; p < .001). Group 3 showed marked olfactory stem cell under a fluorescence microscope. Conclusion: This study suggests that olfactory stem cells may be used as a potent cellular therapy for accelerating the regeneration of peripheral nerve injuries. © 2016 Wiley Periodicals, Inc. Head Neck 38 : E2011–E2020, 2016